Contemporary facets of business successes among leading companies, operating in Bulgaria - Kiril Dimitrov (Vanguard Scientific Instruments in Management, 2013)
The current article unveils and analyzes some important factors, influencing diversity in strategic decision-making approaches in local companies. Researcher's attention is oriented to survey important characteristics of the strategic moves, undertaken by leading companies in Bulgaria.
Keywords: L100; L190; L200; L210; 330; corporate strategy; business strategy; business organizations; strategic management; crisis management